The Impact of Emotional Intelligence on History Subject Achievement of Secondary School Students: Quasi Experimental - Yusoff, Ros Saidatunnaziah Md; Yaacob, Nik Rosila Nik; Abdullah, Melissa Ng Lee Yen (School of Social Sciences, USM, 2017)
The study investigated the impact of emotional intelligence on academic achievement of secondary school students in Kota Setar, Malaysia. The purpose of the study was to examine the relationship between emotional intelligence and academic achievement among secondary school students. A sample of 173 participants randomly selected from four secondary schools was used. The schools were randomly assigned to the two treatment conditions (with and without emotional intelligence activities module) and control group. Questionnaire and achievement test were employed to generate data for the study. Two research hypotheses were formulated to guide the study. The hypotheses were tested using descriptive statistical method, split plot ANOVA (SPANOVA). The study revealed that there is a positive relationship between emotional intelligence skills and academic achievement such that developing emotional intelligence skills of a student will lead to the enhancement of his/her academic achievement. The findings of this study may assist stakeholders in the education sector in developing a better understanding of the effects of emotional intelligence on the academic achievement of secondary school students.